A ictiofauna de riachos responde às alterações da paisagem no Cerrado? – Investigando os sinais sutis da assimetria flutuante - Dennys Heilbuth Cachapuz Drager (2022)
Multiple disturbances of anthropic origin can negatively affect different levels of biological organization and generate unfavorable responses along ecosystems. Several approaches use biological markers to quantify such impacts, including fluctuating asymmetry, which represents subtle, random variations in the bilateral symmetry plane in paired morphological structures, often used as an indicator of developmental instability in organisms under stress conditions. Despite applications in multiple stressors, systems and biological groups, fluctuating asymmetry studies for stream fishes under the perspective of landscape changes are scarce. We conducted the study in fish populations and assemblages of streams from the Brazilian Savanna (i.e, Cerrado), considered one of the most threatened biomes on Earth. We applied an Integrated Disturbance Index, which combines local and catchment-level anthropic impact variables, to define the streams with the most and least degrees of disturbance. Our central hypothesis is that the fluctuating asymmetry level of the ichthyofauna, assessed from three morphometric and two meristic traits, is greater in most disturbed sites. We found no differences in FA levels at the community level by the degree of disturbance. However, we found higher fluctuating asymmetry levels in the pelvic fin length and eye diameter of Knodus moenkausii in most degraded streams. Our findings suggest that stream fish species respond differently to FA sensitivity as an indicator of stress. In addition, we recommend that additional studies must be carried out to understand the ecology and natural history of stream fish species, and how FA varies between different taxonomic and functional groups.